Preparation method and application of aluminum-doped zinc oxide imaging coating
By controlling the aluminum doping amount and treatment process in the preparation of aluminum doped zinc oxide imaging coating, AZO nanopowder and modified nanotitanium dioxide are formed, the lattice defect problem caused by excessive aluminum doping is solved, and the coating with low resistivity and high light transmittance is achieved, and the visual effect of the video is improved.
Patent Information
- Application Number
- CN202411980817.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, aluminum-doped zinc oxide is directly used for display screen coatings that are prone to excessive aluminum doping, resulting in lattice defects, reducing carrier concentration and mobility, thereby increasing resistivity and reducing light transmittance, affecting the visual effect of video.
By dissolving ZnCl2 and Al(NO3)3·9H2O in deionized water, adding PEG-2000, high-pressure homogenization was performed, then preparing a mixed alkali solution with NaOH and Na2CO3 as a precipitant, adding dropwise to distilled water for magnetic stirring, controlling the reaction pH and temperature, forming AZO nanopowder and modified nanotitanium dioxide, and finally adding it to the transparent conductive coating in a suitable proportion, and after ultrasonic dispersion and baking and curing treatment, an aluminum-doped zinc oxide imaging coating was prepared.
The low resistivity (5.1×10-4Ω·cm) and high light transmittance (93.5%) of aluminum-doped zinc oxide imaging coating are achieved, with good optical and electrical stability, and the visual effect of the video is improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating materials, and in particular relates to a preparation method and application of an aluminum-doped zinc oxide imaging coating. Background Art
[0002] With the rapid development of information technology, display screens, as information terminal display carriers, play an irreplaceable and important role in the effective dissemination of information. Transparent display screens are an important direction for the development of future display technology, and some mature transparent display products have already appeared in daily life.
[0003] In the field of transparent display, a lot of research on transparent oxide semiconductors (TOS) has been reported in the academic community over the past few decades. However, most researchers only apply transparent oxides to the semiconductor layer and dielectric layer of TFT. The opaque metal electrode in TFT is the main factor that reduces the transmittance of the device. At present, transparent electrodes are almost entirely dependent on indium tin oxide (ITO), indium-doped zinc oxide (IZO) or other indium-containing oxides. These indium-containing materials will lead to high costs and environmental pollution, which is not conducive to green environmental protection and sustainable development. Therefore, a large number of researchers are committed to the development of indium-free transparent electrodes, such as silver nanowires, carbon nanotubes, gallium-doped zinc oxide (GZO) and aluminum-doped zinc oxide (AZO). Among them, AZO materials are expected to replace mainstream indium-based transparent oxides due to their advantages such as transparency, conductivity, abundant resources, low cost and non-toxicity.
[0004] Directly using aluminum-doped zinc oxide for display screen coatings can easily lead to excessive aluminum doping, resulting in lattice defects, reducing carrier concentration and mobility, thereby increasing resistivity and causing a decrease in transmittance and increasing surface roughness, thereby affecting the visual effect of the video.
[0005] Based on this, we proposed a preparation method and application of aluminum-doped zinc oxide imaging coating, hoping to solve the shortcomings of the existing technology. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and application of an aluminum-doped zinc oxide imaging coating in view of the existing problems.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for preparing an aluminum-doped zinc oxide imaging coating comprises the following steps:
[0009] S1. Dissolve ZnCl2 and Al(NO3)3·9H2O in deionized water, add PEG-2000 and place in a microfluidizer for high-pressure homogenization. After completion, take out the homogenized product for later use;
[0010] S2, NaOH and Na2CO3 are prepared into a mixed alkaline solution according to n(NaOH):n(Na2CO3)=2:1 as a precipitant, and the precipitant and the above homogeneous product are added dropwise into distilled water under magnetic stirring at 100-200rpm to ensure that pH=8 during the reaction process, react at 60-70°C for 2-3h, stand and age for 2h, filter, wash with deionized water 5-7 times, wash with anhydrous ethanol 1-3 times, and then place in a vacuum drying oven at 30-40°C to dry to constant weight, and then place in a tubular furnace, keep warm at 300°C for 2h, keep warm at 800°C for 2h, collect the powder for later use;
[0011] S3, subjecting the powder collected in step S2 to ultrafine grinding and then placing it in an RF plasma device for cold plasma treatment to obtain AZO nanopowder;
[0012] S4, placing nano titanium dioxide in an RF plasma device for cold plasma treatment, and then adding it to tetrahydrofuran with ferric chloride at a mass ratio of 1:0.2-0.3, stirring and mixing at 80-90°C, 300-500rpm to obtain dispersion I, and then adding thiophene and 3-vinylthiophene to tetrahydrofuran at a mass ratio of 1:0.4-0.5, stirring and mixing at 70-80°C, 300-500rpm to obtain dispersion II; then adding dispersion I to dispersion II while stirring, stirring and treating at 2-4°C, 200-300rpm for 16-18h, centrifuging, washing with deionized water 2-4 times, and placing in a vacuum drying oven, drying to constant weight at 20-30°C, and placing in a muffle furnace, calcining for 2-3h to obtain modified nano titanium dioxide;
[0013] S5, weigh corresponding weight portions of AZO nano powder 13-15 parts, modified nano titanium dioxide 4-6 parts, polycaprolactone diol 10-12 parts, 2,2-dihydroxymethyl propionic acid 2-3 parts, polytetrahydrofuran diol 23-25 parts, isophorone diisocyanate 26-30 parts, 3-hydroxymethyl propane 2-3 parts, dibutyl tin dilaurate 0.01-0.015 parts, and deionized water 100-120 parts for standby use;
[0014] S6, weighing polycaprolactone diol, 2,2-dihydroxymethyl propionic acid, polytetrahydrofuran diol, isophorone diisocyanate, and dibutyltin dilaurate in step S5, adding them into a reaction kettle, stirring evenly, heating to 99-103° C., reacting for 2-3 hours, adding AZO nanopowder and modified nano titanium dioxide, stirring and mixing evenly, reacting at a constant temperature for 1-2 hours, cooling to 50-60° C., adding deionized water, stirring and dispersing evenly at high speed, adding 3-hydroxymethylpropane, ultrasonically dispersing for 1-2 hours, and stirring at 50-70° C. for 4-6 hours to obtain a transparent conductive coating;
[0015] S7. Evenly apply the obtained transparent conductive coating onto the substrate, and then bake and solidify it.
[0016] Preferably, the working pressure during the high-pressure homogenization treatment in step S1 is 100 MPa.
[0017] Preferably, the rotation speed during the ultrafine grinding in step S3 is 8000-10000 rpm.
[0018] Preferably, during the cold plasma treatment in step S3, the treatment power is controlled to be 300-500 W, the gas flow rate is 2.8-3 L / min, and the treatment time is 3-8 min.
[0019] Preferably, during the centrifugal treatment in step S4, the rotation speed is controlled at 8000-10000 rpm, the temperature is 4-8° C., and the centrifugal treatment time is 20-30 min.
[0020] Preferably, the calcination temperature in step S4 is 460-560°C.
[0021] Preferably, the rotation speed of the high-speed stirring in step S6 is 4000-6000 rpm.
[0022] Preferably, the baking and curing temperature in step S7 is 120-130°C.
[0023] A display screen comprises a transparent conductive coating, wherein the transparent conductive coating is the above-mentioned aluminum-doped zinc oxide imaging coating.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] The present invention provides an aluminum-doped zinc oxide imaging coating, which is greatly improved on the basis of the prior art. By adding specially prepared AZO nanopowder and modified nano-titanium dioxide into the coating in a suitable proportion, the resistivity of the formed coating is as low as 5.1×10 -4 Ω·cm, the transmittance is as high as 93.5%, and it has good optical and electrical stability. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] A method for preparing an aluminum-doped zinc oxide imaging coating comprises the following steps:
[0029] S1. Dissolve ZnCl2 and Al(NO3)3·9H2O in deionized water, add PEG-2000 and place in a microfluidizer for 100MPa high pressure homogenization. After completion, take out the homogenized product for later use;
[0030] S2, NaOH and Na2CO3 are prepared into a mixed alkaline solution according to n(NaOH):n(Na2CO3)=2:1 as a precipitant, and the precipitant and the above homogeneous product are added dropwise into distilled water under magnetic stirring at 100rpm to ensure that pH=8 during the reaction process, react at 60°C for 2h, stand and age for 2h, filter, wash with deionized water 5 times, wash with anhydrous ethanol once, and then place in a vacuum drying oven at 30°C to constant weight, place in a tubular furnace, keep warm at 300°C for 2h, and keep warm at 800°C for 2h, collect the powder for later use;
[0031] S3, placing the powder collected in step S2 in an ultrafine grinder, ultrafine grinding at 8000 rpm, and then placing it in an RF plasma device for cold plasma treatment, with a treatment power of 300 W and a gas flow rate of 2.8 L / min, and treating for 3 minutes to obtain AZO nanopowder;
[0032] S4, placing nano titanium dioxide in an RF plasma device for cold plasma treatment, and then adding it to tetrahydrofuran with ferric chloride at a mass ratio of 1:0.2, stirring and mixing at 80°C and 300rpm to obtain dispersion I, and then adding thiophene and 3-vinylthiophene to tetrahydrofuran at a mass ratio of 1:0.4, stirring and mixing at 70°C and 300rpm to obtain dispersion II; then adding dispersion I to dispersion II while stirring, stirring at 2°C and 200rpm for 16h, rotating speed 8000rpm, temperature 4°C, centrifugal treatment time 20min, washing with deionized water twice, placing in a vacuum drying oven, drying to constant weight at 20°C, placing in a muffle furnace, and calcining at 460°C for 2h to obtain modified nano titanium dioxide;
[0033] S5, weigh corresponding weight portions of AZO nano powder 13 parts, modified nano titanium dioxide 4 parts, polycaprolactone diol 10 parts, 2,2-dihydroxymethyl propionic acid 2 parts, polytetrahydrofuran diol 23 parts, isophorone diisocyanate 26 parts, 3-hydroxymethylpropane 2 parts, dibutyl tin dilaurate 0.01 parts, and deionized water 100 parts for standby use;
[0034] S6, weighing polycaprolactone diol, 2,2-dimethylol propionic acid, polytetrahydrofuran diol, isophorone diisocyanate, and dibutyltin dilaurate in step S5, adding them into a reaction kettle, stirring evenly, heating to 99° C., reacting for 2, adding AZO nanopowder and modified nano titanium dioxide, stirring and mixing evenly, reacting at a constant temperature for 1 hour, cooling to 50° C., adding deionized water, stirring at 4000 rpm, dispersing evenly, adding 3-hydroxymethylpropane, ultrasonically dispersing for 1 hour, stirring at 50° C. for 4 hours to obtain a transparent conductive coating;
[0035] S7. The obtained transparent conductive coating is evenly coated on a glass substrate with a thickness of 1.2 mm, and then baked at 120° C. for curing.
[0036] Example 2
[0037] A method for preparing an aluminum-doped zinc oxide imaging coating comprises the following steps:
[0038] S1. Dissolve ZnCl2 and Al(NO3)3·9H2O in deionized water, add PEG-2000 and place in a microfluidizer for 100MPa high pressure homogenization. After completion, take out the homogenized product for later use;
[0039] S2, NaOH and Na2CO3 are prepared into a mixed alkaline solution according to n(NaOH):n(Na2CO3)=2:1 as a precipitant, and the precipitant and the above homogeneous product are added dropwise into distilled water under magnetic stirring at 150rpm to ensure that pH=8 during the reaction process, and the temperature is 65°C for reaction for 2.5h, and then it is allowed to stand for aging for 2h, and then filtered and washed with deionized water 6 times, and washed with anhydrous ethanol 2 times, and then placed in a vacuum drying oven at 35°C to constant weight, and then placed in a tubular furnace, kept warm at 300°C for 2h, and kept warm at 800°C for 2h, and the powder is collected for standby use;
[0040] S3, placing the powder collected in step S2 in an ultrafine grinder, ultrafine grinding at 9000 rpm, and then placing it in an RF plasma device for cold plasma treatment, with a treatment power of 400 W and a gas flow rate of 2.9 L / min, and treating for 6 minutes to obtain AZO nanopowder;
[0041] S4, placing nano titanium dioxide in an RF plasma device for cold plasma treatment, and then adding it to tetrahydrofuran with ferric chloride at a mass ratio of 1:0.25, stirring and mixing at 85°C and 400rpm to obtain dispersion I, and then adding thiophene and 3-vinylthiophene to tetrahydrofuran at a mass ratio of 1:0.4.5, stirring and mixing at 75°C and 400rpm to obtain dispersion II; then adding dispersion I to dispersion II while stirring, stirring at 3°C and 250rpm for 17h, rotating speed 9000rpm, temperature 6°C, centrifugal treatment time 25min, washing with deionized water 3 times, placing in a vacuum drying oven, drying to constant weight at 25°C, placing in a muffle furnace, and calcining at 510°C for 2.5h to obtain modified nano titanium dioxide;
[0042] S5, weigh corresponding weight portions of AZO nano powder 14 parts, modified nano titanium dioxide 5 parts, polycaprolactone diol 11 parts, 2,2-dihydroxymethyl propionic acid 2.5 parts, polytetrahydrofuran diol 24 parts, isophorone diisocyanate 28 parts, 3-hydroxymethylpropane 2.5 parts, dibutyl tin dilaurate 0.025 parts, and deionized water 110 parts for standby use;
[0043] S6, weighing polycaprolactone diol, 2,2-dihydroxymethyl propionic acid, polytetrahydrofuran diol, isophorone diisocyanate, and dibutyltin dilaurate in step S5, adding them into a reaction kettle, stirring evenly, heating to 101° C., reacting for 2.5 hours, adding AZO nanopowder and modified nano titanium dioxide, stirring and mixing evenly, reacting at a constant temperature for 1.5 hours, cooling to 55° C., adding deionized water, stirring at 5000 rpm, and dispersing evenly, adding 3-hydroxymethylpropane, ultrasonically dispersing for 1.5 hours, and stirring at 60° C. for 5 hours to obtain a transparent conductive coating;
[0044] S7. The obtained transparent conductive coating is evenly coated on a glass substrate with a thickness of 1.2 mm, and then baked at 125° C. for curing.
[0045] Example 3
[0046] A method for preparing an aluminum-doped zinc oxide imaging coating comprises the following steps:
[0047] S1. Dissolve ZnCl2 and Al(NO3)3·9H2O in deionized water, add PEG-2000 and place in a microfluidizer for 100MPa high pressure homogenization. After completion, take out the homogenized product for later use;
[0048] S2, NaOH and Na2CO3 are prepared into a mixed alkaline solution according to n(NaOH):n(Na2CO3)=2:1 as a precipitant, and the precipitant and the above homogeneous product are added dropwise into distilled water under magnetic stirring at 200rpm to ensure that pH=8 during the reaction process, react at 70°C for 3h, stand and age for 2h, filter, wash with deionized water 7 times, wash with anhydrous ethanol 3 times, and then place in a vacuum drying oven at 40°C to dry to constant weight, and then place in a tubular furnace, keep warm at 300°C for 2h, and keep warm at 800°C for 2h, collect the powder for later use;
[0049] S3, placing the powder collected in step S2 in an ultrafine grinder, ultrafine grinding at 10000 rpm, and then placing it in an RF plasma device for cold plasma treatment, with a treatment power of 500 W and a gas flow rate of 3 L / min, and treating for 8 min to obtain AZO nanopowder;
[0050] S4, placing nano titanium dioxide in an RF plasma device for cold plasma treatment, and then adding it to tetrahydrofuran with ferric chloride at a mass ratio of 1:0.3, stirring and mixing at 90°C and 500rpm to obtain dispersion I, and then adding thiophene and 3-vinylthiophene to tetrahydrofuran at a mass ratio of 1:0.5, stirring and mixing at 80°C and 500rpm to obtain dispersion II; then adding dispersion I to dispersion II while stirring, stirring at 4°C and 300rpm for 18h, rotating speed 10000rpm, temperature 8°C, centrifugal treatment time 30min, washing with deionized water 4 times, placing in a vacuum drying oven, drying to constant weight at 30°C, placing in a muffle furnace, and calcining at 560°C for 3h to obtain modified nano titanium dioxide;
[0051] S5, weigh corresponding weight portions of AZO nano powder 15 parts, modified nano titanium dioxide 6 parts, polycaprolactone diol 12 parts, 2,2-dihydroxymethyl propionic acid 3 parts, polytetrahydrofuran diol 25 parts, isophorone diisocyanate 30 parts, 3-hydroxymethylpropane 3 parts, dibutyl tin dilaurate 0.015 parts, and deionized water 120 parts for standby use;
[0052] S6, weighing polycaprolactone diol, 2,2-dihydroxymethyl propionic acid, polytetrahydrofuran diol, isophorone diisocyanate, and dibutyltin dilaurate in step S5, adding them into a reaction kettle, stirring evenly, heating to 103° C., reacting for 3 hours, adding AZO nanopowder and modified nano titanium dioxide, stirring and mixing evenly, reacting at a constant temperature for 2 hours, cooling to 50-60° C., adding deionized water, stirring at 6000 rpm, and dispersing evenly, adding 3-hydroxymethylpropane, ultrasonically dispersing for 2 hours, and stirring at 70° C. for 6 hours to obtain a transparent conductive coating;
[0053] S7. The obtained transparent conductive coating is evenly coated on a glass substrate with a thickness of 1.2 mm, and then baked at 130° C. for curing.
[0054] Comparative Example 1
[0055] A method for preparing an aluminum-doped zinc oxide imaging coating comprises the following steps:
[0056] S1. Dissolve ZnCl2 and Al(NO3)3·9H2O in deionized water, add PEG-2000 and place in a microfluidizer for 100MPa high pressure homogenization. After completion, take out the homogenized product for later use;
[0057] S2, NaOH and Na2CO3 are prepared into a mixed alkaline solution according to n(NaOH):n(Na2CO3)=2:1 as a precipitant, and the precipitant and the above homogeneous product are added dropwise into distilled water under magnetic stirring at 150rpm to ensure that pH=8 during the reaction process, and the temperature is 65°C for 2.5h, and then the reaction is allowed to stand for 2h, and then filtered, washed with deionized water 6 times, washed with anhydrous ethanol 2 times, and then placed in a vacuum drying oven at 35°C to constant weight, and then placed in a tubular furnace, kept at 300°C for 2h, and kept at 800°C for 2h, and AZO nanopowder is collected;
[0058] S3, placing nano titanium dioxide in an RF plasma device for cold plasma treatment, and then adding it to tetrahydrofuran with ferric chloride at a mass ratio of 1:0.25, stirring and mixing at 85°C and 400rpm to obtain dispersion I, and then adding thiophene and 3-vinylthiophene to tetrahydrofuran at a mass ratio of 1:0.4.5, stirring and mixing at 75°C and 400rpm to obtain dispersion II; then adding dispersion I to dispersion II while stirring, stirring at 3°C and 250rpm for 17h, rotating speed 9000rpm, temperature 6°C, centrifugal treatment time 25min, washing with deionized water 3 times, placing in a vacuum drying oven, drying to constant weight at 25°C, placing in a muffle furnace, and calcining at 510°C for 2.5h to obtain modified nano titanium dioxide;
[0059] S4, weigh corresponding weight portions of AZO nanopowder 14 parts, modified nano titanium dioxide 5 parts, polycaprolactone diol 11 parts, 2,2-dihydroxymethylpropionic acid 2.5 parts, polytetrahydrofuran diol 24 parts, isophorone diisocyanate 28 parts, 3-hydroxymethylpropane 2.5 parts, dibutyl tin dilaurate 0.025 parts, and deionized water 110 parts for later use;
[0060] S5, weighing polycaprolactone diol, 2,2-dihydroxymethyl propionic acid, polytetrahydrofuran diol, isophorone diisocyanate, and dibutyl tin dilaurate in step S4, adding them into a reaction kettle, stirring evenly, heating to 101° C., reacting for 2.5 hours, adding AZO nanopowder and modified nano titanium dioxide, stirring and mixing evenly, reacting at a constant temperature for 1.5 hours, cooling to 55° C., adding deionized water, stirring at 5000 rpm, and dispersing evenly, adding 3-hydroxymethylpropane, ultrasonically dispersing for 1.5 hours, and stirring at 60° C. for 5 hours to obtain a transparent conductive coating;
[0061] S6. The obtained transparent conductive coating is evenly coated on a glass substrate with a thickness of 1.2 mm, and then baked at 125° C. for curing.
[0062] Comparative Example 2
[0063] A method for preparing an aluminum-doped zinc oxide imaging coating comprises the following steps:
[0064] S1. Dissolve ZnCl2 and Al(NO3)3·9H2O in deionized water, add PEG-2000 and place in a microfluidizer for 100MPa high pressure homogenization. After completion, take out the homogenized product for later use;
[0065] S2, NaOH and Na2CO3 are prepared into a mixed alkaline solution according to n(NaOH):n(Na2CO3)=2:1 as a precipitant, and the precipitant and the above homogeneous product are added dropwise into distilled water under magnetic stirring at 150rpm to ensure that pH=8 during the reaction process, and the temperature is 65°C for reaction for 2.5h, and then it is allowed to stand for aging for 2h, and then filtered and washed with deionized water 6 times, and washed with anhydrous ethanol 2 times, and then placed in a vacuum drying oven at 35°C to constant weight, and then placed in a tubular furnace, kept warm at 300°C for 2h, and kept warm at 800°C for 2h, and the powder is collected for standby use;
[0066] S3, placing the powder collected in step S2 in an ultrafine grinder, ultrafine grinding at 9000 rpm, and then placing it in an RF plasma device for cold plasma treatment, with a treatment power of 400 W and a gas flow rate of 2.9 L / min, and treating for 6 minutes to obtain AZO nanopowder;
[0067] S4, weigh corresponding weight portions of AZO nano powder 14 parts, nano titanium dioxide 5 parts, polycaprolactone diol 11 parts, 2,2-dihydroxymethyl propionic acid 2.5 parts, polytetrahydrofuran diol 24 parts, isophorone diisocyanate 28 parts, 3-hydroxymethylpropane 2.5 parts, dibutyl tin dilaurate 0.025 parts, and deionized water 110 parts for later use;
[0068] S5, weighing polycaprolactone diol, 2,2-dihydroxymethyl propionic acid, polytetrahydrofuran diol, isophorone diisocyanate, and dibutyl tin dilaurate in step S4, adding them into a reaction kettle, stirring evenly, heating to 101° C., reacting for 2.5 hours, adding AZO nanopowder and modified nano titanium dioxide, stirring and mixing evenly, reacting at a constant temperature for 1.5 hours, cooling to 55° C., adding deionized water, stirring at 5000 rpm, and dispersing evenly, adding 3-hydroxymethylpropane, ultrasonically dispersing for 1.5 hours, and stirring at 60° C. for 5 hours to obtain a transparent conductive coating;
[0069] S6. The obtained transparent conductive coating is evenly coated on a glass substrate with a thickness of 1.2 mm, and then baked at 125° C. for curing.
[0070] Comparative Example 3
[0071] A method for preparing an aluminum-doped zinc oxide imaging coating comprises the following steps:
[0072] S1. Dissolve ZnCl2 and Al(NO3)3·9H2O in deionized water, add PEG-2000 and place in a microfluidizer for 100MPa high pressure homogenization. After completion, take out the homogenized product for later use;
[0073] S2, NaOH and Na2CO3 are prepared into a mixed alkaline solution according to n(NaOH):n(Na2CO3)=2:1 as a precipitant, and the precipitant and the above homogeneous product are added dropwise into distilled water under magnetic stirring at 150rpm to ensure that pH=8 during the reaction process, and the temperature is 65°C for reaction for 2.5h, and then it is allowed to stand for aging for 2h, and then filtered and washed with deionized water 6 times, and washed with anhydrous ethanol 2 times, and then placed in a vacuum drying oven at 35°C to constant weight, and then placed in a tubular furnace, kept warm at 300°C for 2h, and kept warm at 800°C for 2h, and the powder is collected for standby use;
[0074] S3, placing the powder collected in step S2 in an ultrafine grinder, ultrafine grinding at 9000 rpm, and then placing it in an RF plasma device for cold plasma treatment, with a treatment power of 400 W and a gas flow rate of 2.9 L / min, and treating for 6 minutes to obtain AZO nanopowder;
[0075] S4, weigh corresponding weight portions of AZO nanopowder 14 parts, polycaprolactone diol 11 parts, 2,2-dimethylolpropionic acid 2.5 parts, polytetrahydrofuran diol 24 parts, isophorone diisocyanate 28 parts, 3-hydroxymethylpropane 2.5 parts, dibutyltin dilaurate 0.025 parts, and deionized water 110 parts for later use;
[0076] S5, weighing polycaprolactone diol, 2,2-dihydroxymethyl propionic acid, polytetrahydrofuran diol, isophorone diisocyanate, and dibutyl tin dilaurate in step S4, adding them into a reaction kettle, stirring evenly, heating to 101° C., reacting for 2.5 hours, adding AZO nanopowder and modified nano titanium dioxide, stirring and mixing evenly, reacting at a constant temperature for 1.5 hours, cooling to 55° C., adding deionized water, stirring at 5000 rpm, and dispersing evenly, adding 3-hydroxymethylpropane, ultrasonically dispersing for 1.5 hours, and stirring at 60° C. for 5 hours to obtain a transparent conductive coating;
[0077] S6. The obtained transparent conductive coating is evenly coated on a glass substrate with a thickness of 1.2 mm, and then baked at 125° C. for curing.
[0078] Performance Test:
[0079] The performance of the aluminum-doped zinc oxide imaging coatings of Examples 1 to 3 and Comparative Examples 1 to 3 was tested. The specific test results are shown in Table 1 below:
[0080] Table 1
[0081] Adhesion <![CDATA[Resistivity (×10 -4 Ω·cm)]]> Visible light transmittance (%) Example 1 qualified 5.7 92.9 Example 2 qualified 5.1 93.2 Example 3 qualified 6.2 93.5 Comparative Example 1 qualified 7.6 90.9 Comparative Example 2 qualified 8.7 87.9 Comparative Example 3 qualified 10.1 86.6
[0082] It can be seen from Table 1 above that the aluminum-doped zinc oxide imaging coating of the present invention not only has good conductivity, but also has good light transmittance. The comparison between the examples and the comparative examples shows that the AZO nanopowder and modified nano-titanium dioxide of the present invention can give the coating excellent conductivity and light transmittance.
[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing an aluminum-doped zinc oxide imaging coating, characterized in that: The steps include: S1. Dissolve ZnCl2 and Al(NO3)3·9H2O in deionized water, add PEG-2000 and place in a microfluidizer for high-pressure homogenization. After completion, take out the homogenized product for later use; S2, NaOH and Na2CO3 are prepared into a mixed alkaline solution according to n(NaOH):n(Na2CO3)=2:1 as a precipitant, and the precipitant and the above homogeneous product are added dropwise into distilled water under magnetic stirring at 100-200rpm to ensure that pH=8 during the reaction process, react at 60-70°C for 2-3h, stand and age for 2h, filter, wash with deionized water 5-7 times, wash with anhydrous ethanol 1-3 times, and then place in a vacuum drying oven at 30-40°C to dry to constant weight, and then place in a tubular furnace, keep warm at 300°C for 2h, keep warm at 800°C for 2h, collect the powder for later use; S3, subjecting the powder collected in step S2 to ultrafine grinding and then placing it in an RF plasma device for cold plasma treatment to obtain AZO nanopowder; S4, placing nano titanium dioxide in an RF plasma device for cold plasma treatment, and then adding it to tetrahydrofuran with ferric chloride at a mass ratio of 1:0.2-0.3, stirring and mixing at 80-90°C, 300-500rpm to obtain dispersion I, and then adding thiophene and 3-vinylthiophene to tetrahydrofuran at a mass ratio of 1:0.4-0.5, stirring and mixing at 70-80°C, 300-500rpm to obtain dispersion II; then adding dispersion I to dispersion II while stirring, stirring and treating at 2-4°C, 200-300rpm for 16-18h, centrifuging, washing with deionized water 2-4 times, and placing in a vacuum drying oven, drying to constant weight at 20-30°C, and placing in a muffle furnace, calcining for 2-3h to obtain modified nano titanium dioxide; S5, weigh corresponding weight portions of AZO nano powder 13-15 parts, modified nano titanium dioxide 4-6 parts, polycaprolactone diol 10-12 parts, 2,2-dihydroxymethyl propionic acid 2-3 parts, polytetrahydrofuran diol 23-25 parts, isophorone diisocyanate 26-30 parts, 3-hydroxymethyl propane 2-3 parts, dibutyl tin dilaurate 0.01-0.015 parts, and deionized water 100-120 parts for standby use; S6, weighing polycaprolactone diol, 2,2-dihydroxymethyl propionic acid, polytetrahydrofuran diol, isophorone diisocyanate, and dibutyltin dilaurate in step S5, adding them into a reaction kettle, stirring evenly, heating to 99-103° C., reacting for 2-3 hours, adding AZO nanopowder and modified nano titanium dioxide, stirring and mixing evenly, reacting at a constant temperature for 1-2 hours, cooling to 50-60° C., adding deionized water, stirring and dispersing evenly at high speed, adding 3-hydroxymethylpropane, ultrasonically dispersing for 1-2 hours, and stirring at 50-70° C. for 4-6 hours to obtain a transparent conductive coating; S7. Evenly apply the obtained transparent conductive coating onto the substrate, and then bake and solidify it.
2. The method for preparing an aluminum-doped zinc oxide imaging coating according to claim 1, characterized in that: The working pressure during the high pressure homogenization treatment in step S1 is 100 MPa.
3. The method for preparing an aluminum-doped zinc oxide imaging coating according to claim 1, characterized in that: The rotation speed during the ultrafine grinding described in step S3 is 8000 to 10000 rpm.
4. The method for preparing an aluminum-doped zinc oxide imaging coating according to claim 1, characterized in that: During the cold plasma treatment in step S3, the treatment power is controlled to be 300-500 W, the gas flow rate is 2.8-3 L / min, and the treatment time is 3-8 min.
5. The method for preparing an aluminum-doped zinc oxide imaging coating according to claim 1, characterized in that: During the centrifugal treatment in step S4, the rotation speed is controlled to be 8000-10000 rpm, the temperature is 4-8° C., and the centrifugal treatment time is 20-30 min.
6. The method for preparing an aluminum-doped zinc oxide imaging coating according to claim 1, characterized in that: The calcination temperature in step S4 is 460-560°C.
7. The method for preparing an aluminum-doped zinc oxide imaging coating according to claim 1, characterized in that: The rotation speed of the high-speed stirring in step S6 is 4000-6000 rpm.
8. The method for preparing an aluminum-doped zinc oxide imaging coating according to claim 1, characterized in that: The baking and curing temperature in step S7 is 120-130°C.
9. A display screen, characterized in that: The display screen comprises a transparent conductive coating, and the transparent conductive coating is the aluminum-doped zinc oxide imaging coating according to any one of claims 1 to 8.